Cybersecurity risk management in the industry 4.0 (International Journal of Scientific Research and Management (IJSRM), 2022)
A referential and abstract model will be presented to be applied in risk management on cloud computing and industry ICS platforms in general. we are looking at the types of assessments that are out there, we explore the different approaches and techniques behind information technology systems risk assessments and complexity of conducting industrial control system safely at-risk control level.